(untitled) (Acta Scientiarum. Animal Sciences, 2018)
The objective this study was to evaluate the effect of maniçoba supplementation in sugar cane silage with respect to chemical-bromatological composition and the in vitro degradation kinetics of the silage. This experiment was conducted in a completely randomized design with four treatments (maniçoba levels: 0, 20, 30, and 40%) and six repetitions. Silage samples were analyzed for their chemical-bromatological composition, digestible energy, metabolizable energy, total digestible nutrients, in vitro gas production and degradability parameters. The silage with higher inclusion level had better bromatological composition (p < 0.05) than the silage without maniçoba for CP, NDF, ADF and MM (6.49, 56.64, 38.66 and 4.52% versus 2.21, 70.96, 49.95 and 2.78%). Higher ME content (2.35 MJ kg-1 MS versus 1.85 MJ kg-1 MS), DE (2.87 Mcal kg-1 MS versus 2.25 Mcal kg-1 MS) and TDN (65.16% versus 51.11%), respectively. The highest values for gas production were also observed in silage with added maniçoba due to higher NFC content (34.87%). With an increase in the proportion of maniçoba, there was an increase in the soluble a fraction, b fraction, and thus a higher effective degradability of dry matter (46.56%). The addition of maniçoba improves the nutritive value of sugarcane silage.